A 3‐D numerical study of the thermal evolution of the Moon after cumulate mantle overturn: The importance of rheology and core solidification. Issue 9 (18th September 2013) - Zhang, Nan; Parmentier, E. M.; Liang, Yan
Abstract: [1] Models in which the mantle of the Moon evolves from an initially stratified state following magma ocean solidification and overturn have been applied to address important features of long‐term thermal evolution of the Moon, including convective instability of overturned ilmenite‐bearing cumulates (IBC) at the lunar core‐mantle boundary, generation of mare basalts, core sulfur content and inner core radius, paleomagnetism, and the present‐day mantle structure. Whether a dense overturned IBC‐rich layer at the bottom of the mantle can become thermally unstable to generate a single upwelling is controlled largely by the temperature‐dependence of viscosity (the activation energy). Convective instability of the IBC‐rich layer controls the heat flux out the core and the presence of an internally generated magnetic field. A long period of ( 700 Ma) high positive core‐mantle‐boundary (CMB) heat flux after the instability of the IBC‐rich layer is expected from our models. Present‐day deep mantle temperatures inferred from seismic and gravitational inversion constrain the magnitude of mantle viscosity from 5 × 10 19 to 1 × 10 21 Pa s. The CMB temperature and solidified inner core radius inferred from seismic reflection constrain the core sulfur content. Our evolution models with 5–10 wt % sulfur content can produce the observed 240 km radius inner core at the present day. The asymmetrical distribution of the deep moonquakes only in the nearside mantle could be explained as the remnant structure of the single chemical upwelling generated from IBC‐rich layer. Our evolution model after the overturn results in an early 0.55 km expansion in radius for 1000 Ma due to the radiogenic heating associated with IBC in the deep mantle and may provide a simple explanation for the early expansion inferred from the Gravity Recovery and Interior Laboratory mission. Key Points: Lunar evolution Lunar present‐day mantle and core structures Cumulate mantle overturn